The Daily Drucker - Drucker, Peter F. (HarperCollins Publishers, 2004)
The Daily Drucker provides the inspiration and advice to meet the many challenges we face. With his trademark clarity, vision, and humanity, Drucker sets out his ideas on a broad swath of key topics, from time management, to innovation, to outsourcing, providing useful insights for each day of the year.
Keywords: Management; Motivational; Non-Fiction